2020
DOI: 10.1002/path.5473
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous onset of TNFα‐triggered colonic inflammation depends on functional T lymphocytes, S100A8/A9 alarmins, and MHC H‐2 haplotype

Abstract: Recently, we established a doxycycline-inducible human tumor necrosis factor alpha (TNFα)-transgenic mouse line, ihTNFtg. Non-induced young and elderly mice showed low but constitutive expression of hTNFα due to promoter leakiness. The persistently present hTNFα stimulated endogenous pro-inflammatory mouse mS100A8/A9 alarmins. Secreted mS100A8/A9 in turn induced the expression and release of mouse mTNFα. The continuous upregulation of pro-inflammatory mTNFα and mS100A8/A9 proteins, due to their mutual expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Wu F et al [ 32 ] elucidated that S100A9 upregulated in trinitrobenzene sulfonic acid-induced murine colitis and could be regulated by NF-κB inhibition. Leite Dantas R et al [ 33 ] demonstrated that S100A8/A9 alarmins in one of the determinants of Spontaneous onset of colonic inflammation which triggered TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…Wu F et al [ 32 ] elucidated that S100A9 upregulated in trinitrobenzene sulfonic acid-induced murine colitis and could be regulated by NF-κB inhibition. Leite Dantas R et al [ 33 ] demonstrated that S100A8/A9 alarmins in one of the determinants of Spontaneous onset of colonic inflammation which triggered TNFα.…”
Section: Discussionmentioning
confidence: 99%